Penerapan Akuntansi Pada Usaha Mikro Kecil dan Menengah di Kecamatan Cimanggis Kota Depok - Rosidah Rosidah; Ngatimin Ngatimin (Prisani Cendekia, 2023)
Accounting is an information system that produces reports to interested parties regarding economic activities and company conditions. Until now, there are still many Micro, Small and Medium Enterprises (MSMEs) that support the nation's economy that have not applied accounting in running their businesses. This study aims to identify and analyze the application of accounting for Micro, Small and Medium Enterprises (MSMEs) and the constraints they face. This study took 30 MSMEs in Ciamnggis District, Depok City. This research method is a survey research, research that takes data or information from a sample of a population using questionnaires and interviews as data collection tools. The data were obtained from MSME entrepreneurs in Cimanggis District, Depok City. This research is qualitative in nature. The results showed that most of the MSMEs in the Cimanggis sub-district, Depok City had already recorded sales, purchases of supplies, although in a simple way. The obstacles that hinder MSMEs in implementing accounting include educational background, never having attended accounting training and there are still many actors who do not understand the importance of accounting in their business.